Workplace Stress and Burnout among Employees in High-Technology and Research Institutions: A Review of Nursing Roles and Interventions - Ajesha Musa Paul; Abdullahi Isah Kuba (Darul Yasin Al Sys, 2026)
Workplace stress and burnout represent substantial threats to employee well-being and organizational effectiveness in demanding high-technology and research environments. This systematic review examined the principal causes and consequences of workplace stress and burnout, with particular attention to nursing-led interventions for their prevention and management. Peer-reviewed studies were identified through searches of PubMed, Scopus, and Google Scholar using terms including “workplace stress,” “burnout,” and “nursing interventions.” The reviewed evidence identified organizational, environmental, and psychological stressors as major contributors to burnout. Nursing-led interventions, particularly mindfulness-based stress reduction, cognitive behavioral therapy, and peer-support networks, were associated with reduced emotional exhaustion and improved job satisfaction. However, their implementation was constrained by organizational limitations, workforce adaptation challenges, and ethical concerns surrounding the integration of artificial intelligence into nursing practice. The findings further indicate that effective intervention requires organizational support, appropriate training for nurses in artificial intelligence, and the development of nursing-specific technological tools. This review demonstrates that addressing workplace stress and burnout in high-technology and research institutions requires an integrated approach combining evidence-based psychological interventions, peer support, technological preparedness, and supportive organizational policies. It contributes to the literature by consolidating nursing intervention strategies and identifying implementation priorities for improving employee well-being in technologically intensive workplaces.